Ultrafast dynamics of helical Dirac fermions in the topological insulators - Bai, Ya; Li, Na; Li, Ruxin; Liu, Peng (Advances in physics: X, 2022)
Three-dimensional topological insulators feature unconventional two-dimensional surface states, the carriers in which are helical Dirac fermions and protected from backscattering. Thus, they exhibit novel electronic response upon illuminate ultrashort and intense laser light. We briefly reviewed recent studies on ultrafast phenomena from the surface of the topological insulators driven by laser pulse ranging from visible to THz frequency. Ultrafast dynamics of Dirac fermions can be excited by helical photons and driven by strong light field. Many unique nonlinear behaviors have been demonstrated, such as the excitation of helicity-dependent photocurrent, the formation of Floquet-Bloch bands, lightwave-driven Dirac currents and the generation of optical high-harmonic emission. This review aimed at understanding the microscopic mechanism of the ultrafast charge and spin dynamics in topological surface states and its prospects for coherent manipulation of Dirac fermions by laser light.